ANALISIS FAKTOR-FAKTOR yang MEMPENGARUHI MINAT BELI MIE BALAP di KECAMATAN SIANTAR MARTOBA - SITINJAK, WAHYUNITA (Prodi Agribisnis Fakultas Agro Teknologi Universitas Prima Indonesia, 2021)
The purpose of this study was to determine the factors that influence buying interest in racing noodles in Siantar Martoba District. The object of ths research is consumers who visit the noodle racing stall with a total of 50 respondents. The data analysis method used in this study is multiple linier regression, F test, T test with SPSS 22 tools. The results of the study showed that the independent variable was able to explain the interest in buying racing noodles in Siantar Martoba District by 74.5% while the remaining 25.5% was explained by other factors not examined in this study. Simultaneously or together, all independent variables (business location, product quality, lifestyle, and customer service) have a significant effect on buying interest in racing noodles in Siantar Martoba District with a sig value of 0.000 < 0.05.